2017
DOI: 10.1080/10255842.2017.1293664
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale analysis of the effect of nano-filler particle diameter on the physical properties of CAD/CAM composite resin blocks

Abstract: The objective of this study was to assess the effect of silica nano-filler particle diameters in a computer-aided design/manufacturing (CAD/CAM) composite resin (CR) block on physical properties at the multi-scale in silico. CAD/CAM CR blocks were modeled, consisting of silica nano-filler particles (20, 40, 60, 80, and 100 nm) and matrix (Bis-GMA/TEGDMA), with filler volume contents of 55.161%. Calculation of Young's moduli and Poisson's ratios for the block at macro-scale were analyzed by homogenization. Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…The use of nanofillers has been also demonstrated to impove mechanical characteristics of many biomedical materials, mainly used in orthopedics [24] and dentistry [25]. However, this paper presents the unique results of nanoscale MgO dielectric properties itself, in the temperature and frequency range.…”
Section: Introductionmentioning
confidence: 95%
“…The use of nanofillers has been also demonstrated to impove mechanical characteristics of many biomedical materials, mainly used in orthopedics [24] and dentistry [25]. However, this paper presents the unique results of nanoscale MgO dielectric properties itself, in the temperature and frequency range.…”
Section: Introductionmentioning
confidence: 95%
“…Multi-scale analysis 32,33) enables the investigation of the influence of the multifactorial properties of fillers at micro-or nano-scale on the physical properties at macro-scale 34) . The in silico analysis established in this study, which replaces theoretical analysis with a composite theory such as the modified McGee-McCullough model, in a multi-scale analysis used to calculate the material properties of CR at macro-scale, is applicable to the investigation of the above-mentioned factors, while conventional approaches are not 14,16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Instead of in vitro models, in silico three-dimensional finite-element analysis has been used to predict the properties of resin composite materials, such as resin properties with various filler contents 17) or filler sizes 18) . Yamaguchi et al have confirmed that predicted flexural strengths by in silico analysis was significantly correlated to those obtained by in vitro tests 19) .…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al have confirmed that predicted flexural strengths by in silico analysis was significantly correlated to those obtained by in vitro tests 19) . By using nanoscale properties of CAD/CAM RCB components, including the mechanical properties of silica fillers and resin matrices, macroproperties, such as the elastic modulus and Poisson's ratio of the CAD/CAM RCB can be predicted by homogenization analysis 18,20) . When a force is added to the CAD/CAM RCB at a macroscale, the strain and stress distribution of the CAD/CAM RCB, including the maximum principal strain (MPS), which is known as the failure criteria of composite materials 19,21) at a certain nanoscale area can be analyzed by localization analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation